Exploring the effect of Internet marketing orientation, Learning Orientation and Market Orientation on innovativeness and performance: SME (exporters) perspectives - Aziz, Norzalita A.; Omar, Nor Asiah (Journal of Business Economics and Management, 2013)
This study explores the relationship between Internet Marketing Orientation, Market Orientation, Learning Orientation, Innovation Capabilities and Performance. The study also investigates the role of Internet Marketing Orientation integration in the linkage between Market Orientation-Innovativeness and Learning Orientation-Innovativeness. From an analysis of usable survey data from 101 Bumiputera SMEs-Exporters, three dimensions of Market Orientation (Customer Focus, Inter-Functional Coordination, Information Dissemination), two dimensions of Learning Orientation (Shared Knowledge, and Vision and Commitment to Learning), one dimension of Internet Marketing Orientation and one dimension of Innovation Capabilities and Performance are extracted from the factor analysis results. The results of regression analysis show that Customer Focus, Shared Knowledge and Vision, and Internet Marketing Orientation directly influenced SMEs’ Innovation Capabilities. However, Internet Marketing Orientation is more influential in developing innovation capabilities among SMEs compared to others. While, Shared Knowledge and Vision is the crucial factor in enhancing the business performance among SME (exporters). The relationship among a firm’s Internet Marketing Orientation, Learning Orientation, Market Orientation and Innovation Capabilities and Performance are considered a crucial research area in developing countries. The implications for Malaysian SMEs are discussed.